Second Honey-moon - Schneider, Susan; Rhodes, Sonya (1992)
Contents : Necessary changed,the high-risk woman,the high-risk man,the high-risk marriage,the mid-life affair,sexual renewa,impasses,the joyless marriage,surviving mid-life divorce,the mortal heart,portraits of mid-life marriages: high points,low points,turning points.
Includes bibliographical references and index
Keywords: Married people